The Effect of Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR) And Non-Performing Loans (NPL) on Return on Asset (ROA) In Banking Companies Listed on The Indonesia Stock Exchange During The Period Of 2016-2020 - Tami, Sri Utami Permata; Riska Kumala Dewi (Kirana Publisher (KNPub), 2022)
This study aimed to determine the partial and simultaneous effect of Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR) and Non-Performing Loans (NPL) on Return On Asset (ROA) in banking companies shares listed on the Indonesia Stock Exchange in 2016-2020. The population of this study were all conventional commercial banking companies listed on the Indonesia Stock Exchange in the period of 2016-2020.The sampling technique was carried out by purposive sampling, so that 9 banking companies were obtained as study samples. The data analysis technique used was linear regression analysis by Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR) and Non-Performing Loans (NPL) as independent variable and Return On Asset (ROA) as the dependent variable. The results of this study indicated that Capital Adequacy Ratio (CAR) partially had a significant and positive effect on Return On Asset (ROA), Loan To Deposit Ratio (LDR) had no significant and positive effect on Return On Asset (ROA), and Non-Performing Loans (NPL) had no significant and negative effect on Return On Asset (ROA). While Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR) and Non-Performing Loans (NPL) simultaneously had a significant effect on Return On Asset (ROA).